A Stylistic Study of Subjugation in Quranic Texts - Riyad Tariq Kadhim Al-Ameedi; Aseel Kareem Mohammed Al-Tamimi (Hasanuddin University, 2022)
This is a study of finding the term ‘subjugation’ in Qur’anic texts, which explores the possibility of looking differently to the concept of subjugation in holding some components between the varieties of some Suras that are usually encountered in the Qur’anic texts. It adopts some stylistic techniques from Leech and Short (2007) categorization of figures of speech and Athens (2015) components of subjugation are utilized for the analysis of the data under study. The main aim of this paper is to show how people subjugate to Allah’s message based on force, domination, power and intimidation to control over them and to do what they are told. God intimidates people to worship Him for the purpose of making them feel safety in their life and in the Last Day (Judgment Day). This research used descriptive qualitative method. This paper attempts to identify the stylistic aspects of subjugation in certain Qur’anic texts, study aims at identifying the most common stylistic devices employed in using subjugation, showing the most frequent components of subjugation utilized in such texts and identifying the most frequently types of stylistics. It hypotheses that parallelism, metaphor, rhyme, emphasis and synonymia are more frequently used in Quranic texts, force and domination are the most frequently components employed, and phono-stylistics is the most frequently type of stylistics utilized in Quranic texts.